Strategic Performance and Competitive Edge in the Aviation Industry: Insights from the Balanced Scorecard Approach - Ahmed, Nassar; Ali, Afsar (Revista de turism - studii și cercetări în turism, 2025)
The aviation sector, marked by fierce rivalry, complicated operational dynamics, as well as changing consumer expectations, demands an extensive framework to analyze and enhance its strategic performance. The current study examines the application of the (BSC) framework to evaluate strategic performance, together with a particular emphasis on establishing a competitive advantage in the aviation industry in general. This research examines the link among “key performance indicators” across four domains of the (BSC) “financial, customer, internal processes, and learning & growth” utilizing a sample comprising 388 ground personnel and customers across three different airports throughout Northern India. This research enhances the current literature by providing empirical evidence into the perceptions of ground personnel, a vital operational aspect of aviation, regarding the use of the Balanced Scorecard across their working environment. Finally, the results will make a contribution to both the field of academia along with the practical management practices employed within the aviation sector.